2015
DOI: 10.1007/s10802-015-0091-y
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Maladaptive Parenting Strategies in Families of Adolescent Mothers: Effects from Grandmothers to Young Children

Abstract: The current longitudinal study examined the effect of the transmission of maladaptive parenting strategies from grandmothers to adolescent mothers on children’s subsequent development. Mexican-origin adolescent mothers (N = 204) participated in home interviews when the adolescent’s child (89 boys, 60 girls) was 2, 3, 4, and 5 years old. Grandmothers’ psychological control toward the adolescent mother was positively related to adolescents’ potential for abuse 1 year later, which was subsequently positively rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 97 publications
1
19
0
Order By: Relevance
“…Demographic Risks. Although child maltreatment cuts across all ethnicities and socioeconomic strata (SES), the prevalence of maltreatment has been shown to be higher in minority populations and/or in groups characterized as having low SES (Hussey, Chang, & Kotch, 2006;Sedlak et al, 2010;Stith et al, 2009). SES can be conceptualized as a contextual indicator for other factors that may increase the risk of committing child maltreatment, such as parental psychopathology and early childbearing (Pears & Capaldi, 2001).…”
Section: Measurement Factorsmentioning
confidence: 99%
“…Demographic Risks. Although child maltreatment cuts across all ethnicities and socioeconomic strata (SES), the prevalence of maltreatment has been shown to be higher in minority populations and/or in groups characterized as having low SES (Hussey, Chang, & Kotch, 2006;Sedlak et al, 2010;Stith et al, 2009). SES can be conceptualized as a contextual indicator for other factors that may increase the risk of committing child maltreatment, such as parental psychopathology and early childbearing (Pears & Capaldi, 2001).…”
Section: Measurement Factorsmentioning
confidence: 99%
“…Particularly, continuity across generations of harsh and hostile or aggressive parenting (Bailey, Hill, Oesterle, & Hawkins, ; Conger, Neppl, Kim, & Scaramella, ; Hops, Davis, Leve, & Sheeber, ) and parental monitoring (Capaldi, Pears, Patterson, & Owen, ; Smith & Farrington, ) has been reported. Moreover, continuities across generations are also found for attachment styles (e.g., Seay, Jahromi, Umaña‐Taylor, & Updegraff, ; Verhage et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, several studies have shown an intergenerational transmission of parenting attitudes and behaviors. For example, parents who take a harsh discipline approach to childrearing tend to transmit these beliefs and practices to their children (Seay et al 2016).…”
Section: Introductionmentioning
confidence: 99%